2011
DOI: 10.1590/s1807-59322011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in ankylosing spondylitis-associated cumulative healthcare utilization: a population-based cohort study

Abstract: BACKGROUND:Ankylosing spondylitis (AS) is one of the most common rheumatic diseases with gender differences in prevalence and clinical presentation. This study aimed to examine whether such gender differences are correlated with cumulative healthcare utilization in Taiwan.METHODS:The National Health Insurance Research Database supplied claim records of one million individuals from 1996 to 2007. Selected cases included patients aged ≥16 years. Certified rheumatologists diagnosed the patients in three or more vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…Based on clinical practice and epidemiology, AS is considered to be a male-predominant disease (2). Thus, identifying gender differences in cancer development may affect treatment policies for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on clinical practice and epidemiology, AS is considered to be a male-predominant disease (2). Thus, identifying gender differences in cancer development may affect treatment policies for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects who received a cancer diagnosis (ICD9-CM codes 140-208) were confirmed by following up from the first diagnosis to their regular treatment. In most cases, patients who receive a cancer diagnosis typically undergo regularly scheduled treatment such as surgery, radiotherapy, chemotherapy and/or drug therapy (2,(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation may be that women's who live in this area using health services less or less hospital admissions. 17 In conclusion, although role of HLA B27 in AS etiology has not been fully understood, literature data about HLA B27 positive patients in our country is limited. This study revealed that HLA B27 prevalence in our study is different from the ratio of other study.…”
Section: Discussionmentioning
confidence: 79%
“…Ankylosing spondylitis (AS) is a common immune-mediated inflammatory rheumatic disease affecting 0.11%-0.38% of the Taiwanese population [1,2]. It is characterized by chronic spinal pain, stiffness, fatigue and progressive spinal ankylosis.…”
Section: Introductionmentioning
confidence: 99%